How Children Think and Learn / The Social Contexts of Cognitive Development: Second Edition - Wood David (Blackwell Publishing, 1998)
The writer explores in detail theories and discussions of how children think and learn. Preface, Acknowledgements, Introduction: From Pavlov to Piaget...a Round Trip?, Images of Childhood and Their Reflection in Teaching, A Decade of Development (Maturation and Learning!), Are There Stages of Development?, Learning how to Think and Learn, Language and Learning, Making Sense, The Literate Mind, The Mathematical Mind, Education and Educability, Bibliography, Index.